ANALISIS PENGARUH TINGKAT PERPUTARAN PIUTANG DAN TINGKAT PERPUTARAN PERSEDIAAN TERHADAP RENTABILITAS EKONOMI PADA PT. AFRESH INDONESIA JAMBI - arna suryani (Universitas Batanghari Jambi, 2016)
The purpose of this research is to: (1) determine the level of receivable turnover, (2) determine the level of inventory turnover, (3) determine the level of economic rentability, (4) knowing the influence of reveivable trunover and inventory turn over to wards economic rentability. The object of this research is PT. Afresh Indonesia in Jambi from 2012 to 2014 period.Methods of data collection in this study was done by using documentation technique. The method analysis used descriptive analysis and inferensial analysis. Statistical analysis tool used is multiple linier regretion and hyphotesis testing F and t test. Data processing techniques performed by statistical analysis using SPSS 18.0The hypothesis of this research is receivable turnover and inventory turnover, having significant influence to economic rentability simultaneously and partially. Hypothesis testing is one by F test dan t test. By comparing the coefficient of determinance is know for account receivable turnover amounted 15.8% and inventory turnover amounted to 24.4%. it can be seen that the level of account receivable turn over has more dominant influence on economic rentability.Keywords: Receivables Turnover, Inventory Turnover, Economic Rentability